Comparison of clinical course and therapeutic strategy in patients with isolated myocyte bridges of coronary arteries or combined coronary artery pathology - Z. A. Bagmanova; N. A. Mazur; V. V. Plechev; I. M. Karamova; V. G. Rudenko (Кардиоваскулярная терапия и профилактика)
Aim. To investigate the prevalence of clinically significant myocyte bridges (MB) of coronary arteries (CA) in patients hospitalised with the diagnosis “Coronary heart disease (CHD): effort angina”; to assess the rates of acute coronary syndrome (ACS) and myocardial infarction (MI) in anamnesis among patients with MB and intact CA or CA atherosclerosis (AS), with or without arterial hypertension (AH); to identify the specific features of therapeutic strategies in patients with isolated MB or combined CA pathology. Material and methods. In 2003-2009, coronary angiography (CAG) was performed in 10298 patients. Results. In 364 patients (3,5 %), MB were diagnosed: in Group I (n=114), isolated MB; in Group II (n=59), MB and AH; in Group III (n=105), MB and CA AS; and in Group IV (n=75), MB, CA AS, and AH. Individuals with isolated MB and combined MB did not differ by ACS rates. Acute MI prevalence was significantly higher in patients with MB and CA AS (n=16/105; 15,2 %; p1-3=0,001), as well as in patients with MB, CA AS, and AH (n=9/75; 12 %; p1-4=0,014). The highest anamnestic prevalence of MI was observed among individuals with MB, CA AS, and AH (n=35/75; 47 %; p1-4=0,00; p2-4=0,05; p3-4=0,04). Conclusion. CA MB could result in ACS development among patients with chest pain syndrome. Among patients with MB, acute MI variant of ACS develops significantly more often for the combination of MB and CA AS. Our results suggest that the majority of patients with CA MB require pharmaceutical therapy. When conservative treatment is ineffective, or when MB are combined with CA AS, mammary coronary grafting could be recommended.